ANALYSIS OF CONSUMER BEHAVIOR IN E-COMMERCE IN THE RETAIL SECTOR IN LATIN AMERICA 2020-2025 - Carrasco Muñoz, Claudia Roxana; Arévalo Rioja, Luz Elena; Sánchez Tarrillo, Haydee Filomena; Sono Tantarico, Evelyn; Sagástegui Cruz, Julia Otilia (LACCEI, 2025)
This systematic review analyzed the characteristics of e-commerce and its impact on consumer behavior in the retail sector in Latin America during the period 2020-2025. Rigorous methodological criteria were applied in accordance with the PRISMA methodology, considering 40 studies from Mexico, Brazil, Ecuador and Peru, obtained from academic databases such as Scopus, Google Scholar, Redalyc, etc. The findings revealed an expansion of technological infrastructure in the region, evidenced by the increase in Internet access, the use of digital platforms and electronic means of payment. The adoption of digital technologies improved the user experience, highlighting the importance of adaptive design and web usability in loyalty and purchase intent. The influence of social networks, transaction security and trust in payment methods were key factors in the digital consumer’s decision. The COVID-19 pandemic accelerated the use of digital channels, changing consumer habits. Despite the growth of e-commerce, challenges related to digital inclusion, payment security and access in rural areas persisted. The study showed a higher concentration of research in Mexico and Brazil.